Feature selection by ant colony optimization and experimental assessment analysis of PV panel by reflection of mirrors perpendicularly - Kolamroudi, Mohammad Karimzadeh; Ilkan, Mustafa; Egelioglu, Fuat; Safaei, Babak (Pergamon-Elsevier Science Ltd, 2023)
This study ranks the effective factors in the output power of the low concentrator photovoltaic system (LCPVS) with 4 mirrors using Feature Selection (FS) approach through Ant Colony Optimization (ACO) method based on the analysis of the system improvements in summer and winter. The aim was to improve the intensity of solar irradiation on the same surface area of photovoltaic (PV) panel using mirrors, which led to an increase in power output. The proposed system comprised 4 mirrors that reflected solar radiation to PV panel surface, that was cooled by water spraying, in the most perpendicular position possible. Having done with the related experiments, the results were compared with reference panel. It was demonstrated that the average DC power output of the LCPVS with 4 mirrors was roughly the same, and it was 2.8 times more than that of the reference panel in summer and winter. Moreover, the average DC power output improvement in PV panel was 184.01% in summer and 179.42% in winter. The parameters influencing the output power of PV panel were ranked accordingly by FS approach through ACO. The developed system has the potential to be useful throughout the winter and can also be set up in the majority of regions across the globe.
Keywords: Feature selection; Ant colony optimization; Improvements; PV panel; Power output